2011
DOI: 10.30935/cedtech/6052
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Computer Anxiety and Computer Self-Efficacy

Abstract: This study examined the relationship between computer anxiety and computer selfefficacy of students and teachers in elementary and secondary schools. The sample included a total of 845 subjects from two private school systems in Turkey. The Oetting's Computer Anxiety Scale was used to measure computer anxiety whereas the Murphy's Computer Self-Efficacy Scale was used to measure computer self-efficacy of subjects. The results demonstrated that elementary students were less-anxious than secondary students; males… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 23 publications
5
44
0
6
Order By: Relevance
“…Individual with high level of anxiety, have low self-efficacy. This study reinforces the findings of previous studies showing that computer anxiety negatively affects selfefficacy [22,27].…”
Section: Goodness Of Fitsupporting
confidence: 92%
“…Individual with high level of anxiety, have low self-efficacy. This study reinforces the findings of previous studies showing that computer anxiety negatively affects selfefficacy [22,27].…”
Section: Goodness Of Fitsupporting
confidence: 92%
“…Male students' self-efficacy perception levels were found to be higher than female students. Different researches also reveal that there is a significant relationship between computer proficiency level and gender (Ipek & Acuner, 2011;Simsek, 2011;Cetin, Caliskan & Menzi, 2012;Cetin & Gungor, 2014;Sayginer, 2016). In most of these studies, it was found that the difference was in favor of males.…”
Section: Discussionmentioning
confidence: 99%
“…Por último, en el trabajo de Simsek (2011), la autoeficacia computacional, indicador de un alto desempeño académi-co, se correlaciona negativamente con la ansiedad. Dicho estudio complementa el hallazgo de la presente investigación, pues la ansiedad se reflejó en la intención de uso de Internet para buscar información con fines académicos e investigativos.…”
Section: Discussionunclassified
“…Empero, la validez de un constructo supone la inclusión de factores negativos, como es el caso de la ansiedad y la adic-ción. En este sentido, ambos factores fue-ron incluidos en la especificación del mo-delo, esperando encontrar valores negati-vos (Simsek, 2011). accesible, extensiva y acumulable puede derivar en una patología de ansiedad y adicción que inhibiría la eficiencia, la eficacia y la efec-tividad informativa.…”
Section: Teoría De La Red Internacionalunclassified